Hyperbaric oxygen for treatment of long COVID-19 syndrome (HOT-LoCO): protocol for a randomised, placebo-controlled, double-blind, phase II clinical trial. Issue 11 (2nd November 2022) - Kjellberg, Anders; Abdel-Halim, Lina; Hassler, Adrian; El Gharbi, Sara; Al-Ezerjawi, Sarah; Boström, Emil; Sundberg, Carl Johan; Pernow, John; Medson, Koshiar; Kowalski, Jan H; Rodriguez-Wallberg, Kenny A; Zheng, Xiaowei; et al.
Abstract : Introduction: Long COVID-19, where symptoms persist 12 weeks after the initial SARS-CoV-2-infection, is a substantial problem for individuals and society in the surge of the pandemic. Common symptoms are fatigue, postexertional malaise and cognitive dysfunction. There is currently no effective treatment and the underlying mechanisms are unknown, although several hypotheses exist, with chronic inflammation as a common denominator. In prospective studies, hyperbaric oxygen therapy (HBOT) has been suggested to be effective for the treatment of similar syndromes such as chronic fatigue syndrome and fibromyalgia. A case series has suggested positive effects of HBOT in long COVID-19. This randomised, placebo-controlled clinical trial will explore HBOT as a potential treatment for long COVID-19. The primary objective is to evaluate if HBOT improves health-related quality of life (HRQoL) for patients with long COVID-19 compared with placebo/sham. The main secondary objective is to evaluate whether HBOT improves endothelial function, objective physical performance and short-term HRQoL. Methods and analysis: A randomised, placebo-controlled, double-blind, phase II clinical trial in 80 previously healthy subjects debilitated due to long COVID-19, with low HRQoL. Clinical data, HRQoL questionnaires, blood samples, objective tests and activity metre data will be collected at baseline. Subjects will be randomised to a maximum of 10 treatments with hyperbaric oxygen or sham treatment over 6 weeks. Assessments for safety and efficacy will be performed at 6, 13, 26 and 52 weeks, with the primary endpoint (physical domains in RAND 36-Item Health Survey) and main secondary endpoints defined at 13 weeks after baseline. Data will be reviewed by an independent data safety monitoring board. Ethics and dissemination: The trial is approved by the Swedish National Institutional Review Board (2021–02634) and the Swedish Medical Products Agency (5.1-2020-36673). Positive, negative and inconclusive results will be published in peer-reviewed scientific journals with open access. Trial registration number: NCT04842448 .